2008
DOI: 10.1086/587689
|View full text |Cite
|
Sign up to set email alerts
|

The Blue Straggler Population in the Globular Cluster M53 (NGC 5024): A CombinedHST, LBT, and CFHT Study1

Abstract: We used a proper combination of high-resolution and wide-field multiwavelength observations collected at three different telescopes (HST, LBT, and CFHT) to probe the blue straggler star (BSS) population in the globular cluster M53. Almost 200 BSSs have been identified over the entire cluster extension. The radial distribution of these stars has been found to be bimodal (similar to that of several other clusters) with a prominent dip at $60 00 ($2r c ) from the cluster center. This value turns out to be a facto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 30 publications
(35 reference statements)
5
28
0
Order By: Relevance
“…For V77 (V = 18.478, V − I = 0.433) and V81 (V = 17.454, V − I = 0.815), we were able to perform the conversion of fluxes into magnitudes. The average magnitudes of V77 verifies its location in the BSS region, while V81 is located exactly on the lower red giant branch (see the CMD of Beccari et al 2008a). We are not sure whether there is a blending effect of two stars in this case or V81 (which we identified as USNO-B1.0 1081-0245849) is indeed a peculiar variable.…”
Section: Short-period Variablessupporting
confidence: 53%
See 2 more Smart Citations
“…For V77 (V = 18.478, V − I = 0.433) and V81 (V = 17.454, V − I = 0.815), we were able to perform the conversion of fluxes into magnitudes. The average magnitudes of V77 verifies its location in the BSS region, while V81 is located exactly on the lower red giant branch (see the CMD of Beccari et al 2008a). We are not sure whether there is a blending effect of two stars in this case or V81 (which we identified as USNO-B1.0 1081-0245849) is indeed a peculiar variable.…”
Section: Short-period Variablessupporting
confidence: 53%
“…We note however that there is a suspected BSS (USNO-B1.0 1081-0245846) near V81 which might account for this variability, although we did not detect the corresponding signal in its time-series. The type of the remaining three new short-period variables (V80, V82, and V83) remains unknown, but their blue straggler nature cannot be ruled out (for example, we note that the previously known variable V73 was not identified as a BSS by Beccari et al 2008a). The properties of all 11 short-period variables detected in this study are given in Table 3.…”
Section: Short-period Variablesmentioning
confidence: 82%
See 1 more Smart Citation
“…In Figure 3, we show all three stars, marked accordingly, and their time-domain light curves. When we cross-correlated our list of known variables with the BSS catalog by Beccari et al (2008; see Section 4.7), we found a match with BSS 102387 from the Hubble Space Telescope/ WFPC2/PC sample to within 0. 6 (coordinates of that BSS are between these three stars, closer to a brighter V57_1).…”
Section: Notes On Individual Variablesmentioning
confidence: 89%
“…In the latest 2010 updated version of the catalog of variables in M53 (Clement et al 2001) there are 62 reported RR Lyrae (RRl) stars, 8 suspected long-period semiregular (SR) stars, and 15 reported SX Phe stars. Out of almost 200 blue straggler stars (BSSs) discovered so far in M53, 14% is estimated to be in binary systems (Beccari et al 2008); however, no eclipsing binaries were previously found in this cluster.…”
Section: Introductionmentioning
confidence: 97%